A high-throughput Gaussia luciferase reporter assay for screening potential gasdermin E activators against pancreatic cancer - Yang Liu; Xiaowei Zhang; Ping Zhang; Tingting He; Weitao Zhang; Dingyuan Ma; Ping Li; Jun Chen (Elsevier, 2023)
It is discovered that activated caspase-3 tends to induce apoptosis in gasdermin E (GSDME)-deficient cells, but pyroptosis in GSDME-sufficient cells. The high GSDME expression and apoptosis resistance of pancreatic ductal adenocarcinoma (PDAC) cells shed light on another attractive strategy for PDAC treatment by promoting pyroptosis. Here we report a hGLuc-hGSDME-PCA system for high-throughput screening of potential GSDME activators against PDAC. This screening system neatly quantifies the oligomerization of GSDME-N to characterize whether pyroptosis occurs under the stimulation of chemotherapy drugs. Based on this system, ponatinib and perifosine are screened out from the FDA-approved anti-cancer drug library containing 106 compounds. Concretely, they exhibit the most potent luminescent activity and cause drastic pyroptosis in PDAC cells. Further, we demonstrate that perifosine suppresses pancreatic cancer by promoting pyroptosis via caspase-3/GSDME pathway both in vitro and in vivo. Collectively, this study reveals the great significance of hGLuc-hGSDME-PCA in identifying compounds triggering GSDME-dependent pyroptosis and developing promising therapeutic agents for PDAC.